Perceived quality, perceived risk and customer trust affecting customer loyalty of environmentally friendly electronics products - Marakanon, Lalinthorn; Panjakajornsak, Vinai (My University, 2017)
At present, industrial business competition causes producers to be aware of quality, price, and variety in developing new products to meet the consumers' needs. This research reviewed the literature on green marketing and proposes a new conceptual framework of customer loyalty. It uses four constructs—perceived quality, perceived risk, customer trust, and customer loyalty—in the context of environmentally friendly electronics products in Thailand. This research employed an empirical study using the questionnaire survey method to verify the hypotheses. Data were obtained from 420 consumers who bought and used environmentally friendly electronic products, particularly mobile phones, computers, and laptops using a purposive sampling method. The data were analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). The results showed that perceived risk and customer trust had a direct effect on customer loyalty while perceived quality had an indirect effect on customer loyalty via customer trust. Furthermore, perceived quality had direct effects on perceived risk and customer trust. The results from the final SEM model were used to confirm the proposed relationships among the variables.
Keywords: customer loyalty; customer trust; environmentally friendly electronics products; perceived quality; perceived risk